175k views
1 vote
Solve using the quadratic formula (you must show work) 52 − 2 + 1 = 0

User Roseann
by
5.5k points

1 Answer

2 votes

Answer:

see below

Explanation:

we have


5x^2-2x+1=0

and the quadratic equation is


ax^2+bx+c=0

so we can see that


a=5\\\\b=-2\\\\c=1

and the quadratic formula is


x=(-b+-√(b^2-4ac) )/(2a) it should go this symbol ± instead of +-

so we insert each value


x=(-(-2)+-√((-2)^2-4(5)(1)) )/(2(5)) \\\\x=(2+-√(4-20) )/(10)\\\\x=(2+-√(-16) )/(10) \\\\x=(2+-4i)/(10) \\\\x_1=(2(1+2i))/(2*5) \\\\x_1=(1+2i)/(5) \\\\x_2=(2(1-2i))/(2*5) \\\\x_2=(1-2i)/(5)

i don't know if you already know about imaginary numbers if you do then the answer is all the work

if you don't know, well just go until


x=(2+-√(-16) )/(10)

and say there is no answer to this, because negatives don't have square roots

User Patil Prashanth
by
4.9k points